2017
DOI: 10.1093/carcin/bgx052
|View full text |Cite
|
Sign up to set email alerts
|

Time-caloric restriction inhibits the neoplastic transformation of cirrhotic liver in rats treated with diethylnitrosamine

Abstract: Hepatocellular cancer is the most common type of primary liver cancer. Cirrhosis is the main risk factor that generates this malady. It has been proven that caloric restriction protocols and restricted feeding schedules are protective in experimental carcinogenic models. We tested the influence of a time-caloric restriction protocol (2 h of food access during the daytime for 18 weeks) in an experimental model of cirrhosis-hepatocarcinoma produced by weekly administration of diethylnitrosamine. Our results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Simple steatosis begins in the centrilobular liver zone. The result of Molina-Aguilar et al (18) indicate that time-caloric restriction reduced hepatomegaly and prevented the increase in blood leukocytes promoted by diethylnitrosamine. Also effects of short food restriction on hepatocytes are visible, but the changes after ADL nutrition are more visible in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Simple steatosis begins in the centrilobular liver zone. The result of Molina-Aguilar et al (18) indicate that time-caloric restriction reduced hepatomegaly and prevented the increase in blood leukocytes promoted by diethylnitrosamine. Also effects of short food restriction on hepatocytes are visible, but the changes after ADL nutrition are more visible in our study.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this is the first investigation to describe a direct beneficial effect of long term TRF on early phases of carcinogenesis. It was recently reported that a time-caloric restricted diet could inhibit progression from cirrhosis to hepatocellular carcinoma induced by chronic administration of diethylnitrosamine [45]. However, feeding time in this study was reduced to 2 hours, resulting in a sizeable (~30%) decrease in daily caloric intake.…”
Section: Discussionmentioning
confidence: 76%
“…The percentage and/or number of MDSCs was also reduced in two studies (45,136). The number of total circulating leukocytes and lymphocytes was reduced in two studies (133,140), while increased lymphocyte proliferation was found in another study (141). Among the serum cytokines evaluated, TNFα was reduced in one study (128) and increased in another study (140).…”
Section: Preclinical Findingsmentioning
confidence: 93%